2022
DOI: 10.1016/j.jceh.2021.12.016
|View full text |Cite
|
Sign up to set email alerts
|

Gut Microbiome and Alcohol-associated Liver Disease

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 53 publications
1
15
0
Order By: Relevance
“…It was previously found that smoking can lower gut ( Opstelten et al, 2016 ; Gui et al, 2021 ) and saliva ( Jia et al, 2021 ) microbiome diversity and contribute to the dysbiosis ( Wu et al, 2016 ; Huang and Shi, 2019 ) in these two body sites. Alcohol usage has also previously been closely linked to decreased gut microbiome diversity ( Bajaj, 2019 ; Philips et al, 2022 ) and increased oral ( Fan et al, 2018 ; Liao et al, 2022 ) microbiome diversity. Additionally, alcohol usage is associated with the growth of pathobionts and they can have a long-term effect on the microbiome ( Vetreno et al, 2021 ; Day and Kumamoto, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…It was previously found that smoking can lower gut ( Opstelten et al, 2016 ; Gui et al, 2021 ) and saliva ( Jia et al, 2021 ) microbiome diversity and contribute to the dysbiosis ( Wu et al, 2016 ; Huang and Shi, 2019 ) in these two body sites. Alcohol usage has also previously been closely linked to decreased gut microbiome diversity ( Bajaj, 2019 ; Philips et al, 2022 ) and increased oral ( Fan et al, 2018 ; Liao et al, 2022 ) microbiome diversity. Additionally, alcohol usage is associated with the growth of pathobionts and they can have a long-term effect on the microbiome ( Vetreno et al, 2021 ; Day and Kumamoto, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Alcohol-associated liver disease (ALD) mortality rose between 2006 and 2017 and it is the leading cause of liver transplantation in the United States [39]. Dysbiosis of gut microbiota with an increase in pathobionts and a decrease in beneficial bacteria occurs in patients with ALD [40].…”
Section: Alcohol-associated Liver Diseasementioning
confidence: 99%
“…These include use of FMT in recurrent HE, recurrent sepsis, multidrug resistant infections, severe alcohol-associated hepatitis not amenable for conventional care or liver transplantation and alcohol use disorder. 56…”
Section: Special Treatment Considerations In End Stage Liver Disease ...mentioning
confidence: 99%